Endocrine Apparatus of the Rat Testes in the Adaptation Dynamics to Low Temperatures - Yu. Sayapina, Irina; M. Mandro, Nikolay; V. Trush, Natal'ya; A. Gavrilov, Yuriy; A. Gavrilova, Galina; V. Hibchenov, Lopsondorzho; N. Chubin, Alexey (International Journal of Engineering and Technology, 2018)
Within the framework of the experimental study, new data were obtained on the endocrine apparatus of rat testicles represented by interstitial endocrinocytes, or Leydig cells (CL), in the dynamics of adaptation of the animal body to low temperatures. Using methods of morphological analysis, including both routine and modern methods, it was found that in the early stages of adaptation the ratio of the main morphofunctional types of CL is violated, the index of CL activity decreases, their sizes decrease, resulting in a decrease in the concentration of testosterone in the blood serum. In the course of further adaptation the relative amount of CL reduces, increasing the number of degenerating CL. In the later stages of adaptation, the relative amount of CL remains reduced, the activity index of endocrinocytes increases, compensatory hypertrophy of CL develops, which leads to an increase in the level of testosterone in the blood serumÂ Â